Emotional design : why we love (or hate) everyday things - Norman, Donald A. (Basic Books, 2004)
"Did you ever wonder why cheap wine tastes better in fancy glasses? Or why washing and polishing your car seems to make it drive better? New research has shown that attractive things really do work better." "In the last decade, the design community has made products easier to use, largely due to Donald Norman's The Design of Everyday Things. But as he demonstrates in this book, we don't just use a product, we become emotionally involved with it. Emotional Design demonstrates for the first time the profound influence of this deceptively simple idea." "Don Norman draws on a wealth of examples and the very latest scientific insights in this exploration of the emotional impacts of objects in our everyday world. His The Design of Everyday Things showed why the products we use should not be confusing, irritating, and frustrating. Emotional Design explains why they must also be attractive, pleasurable, and fun."--Jacket